The Impact of Priority School Designation Under ESEA Flexibility in New York State. Issue 1 (2nd January 2020) - Atchison, Drew
Abstract: Prior to the 2012–13 school year, New York and many other states underwent changes to their accountability systems as a result of applying for and being granted waivers from the requirements of the No Child Left Behind Act of 2001. A key component of these new accountability systems, under what is known as ESEA Flexibility or NCLB Waivers, was the designation of the lowest performing 5% of Title I schools as priority schools with the goal of improved performance within three years of receiving their designation. The priority school policy included elements of both accountability and school turnaround to try to improve student outcomes in low performing schools. This study examines the extent to which elementary and middle priority schools in New York State improved in the three years since being designated priority schools. By the end of the 2014–15 school year—the third year of three to show improvement—I find elementary and middle priority schools did not show improvement and, in fact, performed worse than schools just above the cutoff for determining priority school eligibility.